Pengaruh Sisa Lebih Pembiayaan Anggaran, Pendapatan Asli Daerah, Dana Alokasi Umum Dan Dana Alokasi Khusus Terhadap Perilaku Oportunistik Penyusun Anggaran (Studi Kasus Kab/Kota Provinsi Jawa Tengah Periode 2012-2013) - Septiani, Fitria, Dr. Zulfikar, SE, M.Si (2016)
Opportunistic behavior is behavior that is trying to achieve they wish by all means in a way that is illegal. Even though, can lead to principal-agent relationships that occur within a contract eventually lead to the occurrence of adverse selection (hiding information) and moral hazard (abuse of authority). Thus this study aims to examine whether there are opportunistic behavior in budgeting SiLPA, PAD, DAU and DAK. The population used in this study are all APBD Kab / Kota in Central Java province consists of 29 districts and 6 cities. The research sample was determined by purposive sampling method. The samples used were 48 for 2 years so that each of the existing 24 districts / cities, with details of 42 counties and six cities. The hypothesis test uses multiple linear regression analysis. The model results of this study indicate that (1) SiLPA no effect on opportunistic behavior in budgeting at the district / city in Central Java province; (2) PAD opportunistic behavior has no effect on the budget in the District / City in the province of Central Java; (3) DAU significant effect on opportunistic behavior in budgeting at the district / city in Central Java province; (4) DAK significant effect on opportunistic behavior in budgeting at the district / city in Central Java province. Keywords: Surplus Financing Articles (SiLPA), revenue (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK), Opportunistic Behavior Budgetary (OPA)